A comprehensive review on the assessment of the quality and authenticity of the sturgeon species by different analytical techniques. (March 2022) - Vilkova, Daria; Chèné, Christine; Kondratenko, Elena; Karoui, Romdhane
Abstract: The sturgeon species are related to a food delicacy and are known for their rich nutritive properties that are essential for human health since prehistoric times. The intensive decline in wild sturgeon populations has led to an increase of the farmed and hybrid species in aquaculture production. The sturgeon meat contains highly digestible proteins, fats, vitamins and minerals which are influenced by its biodiversity. This review will provide different analytical techniques used for the determination of the quality and authenticity of sturgeon species. To attain these objectives, targeted techniques (chemical, sensory, microbiological, chromatographic, morphological, polymerase chain reaction, and so on) and untargeted ones (fluorescence, and mid-infrared spectroscopies, and so on). The former techniques considered as the official methods used to assess the quality and authenticity of sturgeon are time-consuming and need a trained personnel team, while the latter ones based on the use of fluorescence and mid-infrared spectroscopies are considered rapid, non-destructive, relatively cheap, and environmentally friendly. The use of untargeted techniques as a promising tool is not fully explored in the fish sector, particularly for sturgeon, which needs future research to demonstrate and prove their robustness for the determination of the quality and authenticity of this fish species. Highlights: Use of targeted techniques to characterise the quality and authenticity of sturgeon. Untargeted techniques to determine the quality and authenticity of sturgeon. Recent progress in the determination of the quality and authenticity of sturgeon. More research studies are needed by using untargeted techniques.